PLA/sepiolite and PLA/calcium carbonate nanocomposites: A comparison study. Issue 4 (19th December 2012) - Sabzi, Mohammad; Jiang, Long; Atai, Mohammad; Ghasemi, Ismail
Abstract Polylactic acid (PLA)‐based nanocomposites comprising two different types of nanofillers, i.e. sepiolite (SEP) and nano calcium carbonate (NCC), were prepared by internal mixing and injection molding. Because of the different aspect ratio, surface area, and surface property of the nanofillers, their effects on the morphological, mechanical, dynamic mechanical, rheological, and thermal properties of the nanocomposites were shown to be very different. NCC demonstrated more uniform particle dispersion and matrix compatibility than did SEP because of the former's surface treatment, thus leading to higher strength and strain‐at‐failure of PLA/NCC composites. On the other hand, larger aspect ratio and surface area of SEP caused higher melt viscosity, stronger shear thinning, and better thermal resistance of PLA/SEP composites. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013